Comparative analysis of interactional metadiscursive resources in academic writing by L2 and L1 English writers - Musa Al-Mudhaffari; Supyan Hussin; Imran Ho Abdullah (Universitas Syiah Kuala, 2024)
Interactional Metadicursive Resources (IMRs) are established as the most common rhetorical features that assist writers in achieving interaction with the discourse community. The purpose of this study was to compare the use of IMRs in research articles (RAs) authored by Yemeni L2 writers and L1 English writers, while also examining the extent to which both groups employ these resources to achieve persuasive purposes. Based on Hylands (2019) model, AntConc was used as an analytical tool in a corpus-based methodology to analyze the use of IMRs in their context of use, both quantitatively and qualitatively. Moreover, Swales models were adapted to identify rhetorical moves in the different sections of RAs. The findings indicate that L1 writers tended to use IMRs more frequently and effectively to pursue ethos and pathos. However, Yemeni L2 writers tended to use IMRs sparingly, lacking familiarity with their persuasive role. L1 writers tended to express epistemic and affective stances and used these resources throughout their research, while Yemeni L2 writers tended to focus more on propositional content, using limited IMRs in their writing. Furthermore, unlike L1 English writers, who tended to negotiate their claims in the RA introduction and engage their audience in the RA conclusion, Yemeni L2 writers almost exclusively strengthened their line of argument when initiating and concluding their research. The study concludes by discussing the pedagogical implications of the effective use of IMRs in L2 academic writing.